Preserving natural dentition and enhancing prosthetic rehabilitation with Cu-Sil denture: A case report - Stalin, Mathiyazhagan; Rathee, Manu; Mittal, Surbhi; Tomar, Sarthak Singh; Diwan, Kritika; Balavignesh, Senthilvelpalani (Indonesian Journal of Dental Medicine, 2024)
Background: A specific type of transitional denture called a Cu-Sil denture provides a therapy alternative for people who have a lot of natural teeth still in place and do not want to have them extracted. This is particularly salutary for cases where people may feel tone-conscious about the negative impact of tooth loss on their appearance and emotional well-being. Purpose: The purpose of this case report is to provide prosthetic rehabilitation for a partially edentulous patient while conserving the remaining natural teeth and their supporting structures. Case: With only three teeth (12, 13, and 14) remained in the maxillary arch, a 63-year-old man complained to the department of prosthodontics that he had difficulties speaking and eating since he had been missing both upper and lower teeth for a period of five years. Case management:This case report represents a simple method to fabricate a Cu-Sil denture in a partially edentulous patient. Conclusion: Cu-Sil dentures present a promising alternative for partially edentulous patients, offering a method to preserve and support the remaining natural teeth while providing effective prosthetic rehabilitation. The relining material, silicone, functions as a cushion to support the remaining natural teeth. Additionally, the use of a chairside soft-tissue liner in the basic removable partial denture helps to stabilize and retain the existing natural teeth.